f(x) = −4x + 60
f(x) = 4x + 60
f(x) = −4x + 80
f(x) = 4x + 80
Answer:
C
Step-by-step explanation:
I dont have proof but I promise you its right. :)
Answer:
i cant read it sorry
Step-by-step explanation:
The relationship between the rise of the chair with respect to time is required.
The ski lift chair rises
Every seconds a ski lift chair rises .
Divide by on both sides
The rate of the height increase of the ski lift chair is
Learn more about rate of change:
Answer:
{-1, 1, 3}
Step-by-step explanation:
Given the function
y = (x + 1)/3
The domain are the input value x while the range are the output values given the input value x;
Given the domain {-4, 2, 8}
when x = -4;
y = (-4+1)/3
y = -3/3
y = -1
when x = 2;
y = (2+1)/3
y = 3/3
y = 1
when x = 8;
y = (8+1)/3
y = 9/3
y = 3
Hence the member of the range are {-1, 1, 3}